2012
DOI: 10.1016/j.micinf.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the deletion of the six mce operons in Mycobacterium smegmatis

Abstract: The Mycobacterium smegmatis genome contains six operons designated mce (mammalian cell entry). These operons, which encode membrane and exported proteins, are highly conserved in pathogenic and non-pathogenic mycobacteria. Although the function of the Mce protein family has not yet been established in Mycobacterium smegmatis, the requirement of the mce4 operon for cholesterol utilization and uptake by Mycobacterium tuberculosis has recently been demonstrated. In this study, we report the construction of an M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 21 publications
2
67
0
1
Order By: Relevance
“…The specific function of Mce1 during infection is not clear, but a potential role of Mce1 in importing free mycolic acids was recently proposed (57,84). Mce4 is the best studied Mce transporter, with a shown role in cholesterol import (85,86) and a role in virulence (85,87). Thus, another way that the SecA2 pathway may contribute to M. tuberculosis infection could be through its role in SBP and Mce transporter localization.…”
Section: Differences In Protein Families and Network In The ⌬Seca2mentioning
confidence: 99%
“…The specific function of Mce1 during infection is not clear, but a potential role of Mce1 in importing free mycolic acids was recently proposed (57,84). Mce4 is the best studied Mce transporter, with a shown role in cholesterol import (85,86) and a role in virulence (85,87). Thus, another way that the SecA2 pathway may contribute to M. tuberculosis infection could be through its role in SBP and Mce transporter localization.…”
Section: Differences In Protein Families and Network In The ⌬Seca2mentioning
confidence: 99%
“…strain RHA1, a soil bacterium related to M. tuberculosis, revealed that 51 rhodococcal genes specifically expressed during growth on cholesterol were conserved within an 82-gene cluster in M. tuberculosis H37Rv and Mycobacterium bovis bacillus Calmette-Guerin (BCG). 2 These studies provided the first indication of a cholesterol catabolic pathway critical for intracellular survival, and led to the identification of the Mce4 system, a multi-subunit ABC-like transporter functioning in cholesterol uptake by Rhodococcus, 3 Mycobacterium smegmatis 4 and M. tuberculosis. 5 The Mce4 transporter is essential for survival during the chronic stages of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 Pandey and Sassetti found that M. tuberculosis can grow using cholesterol as a primary carbon source and that the mce4 transporter is required for cholesterol uptake. M. tuberculosis contains four homologous mce operons, mce1-mce4, which are thought to encode lipid transporters [57,58].…”
Section: Lipid Body Formation In M Tuberculosis Is Critically Dependmentioning
confidence: 99%